2018
DOI: 10.20546/ijcmas.2018.712.217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Potassium Management on Soil Biological Properties and Yields of Corn under Corn-Wheat Cropping System

Abstract: Potassium fertilization is often ignored in cereal-based cropping systems assuming sufficient K reserves in the alluvial soils of north-western India. However, the responses to K have now widely reported due to continuous mining and little additions through external sources. Little known on the effects of integrated K management on soil biological properties and yield performance of corn grown in sequence with wheat. A field experiment was conducted during 2010-2012 to find out the performance of corn (Zea may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The improvement in the level of available NPK under VC + MI application might be due to enhanced nutrient release as a result of microbes-mediated accelerated decomposition and mineralization of inoculated manure ( Kuotsu et al, 2014 ; Gupta et al, 2020 ). Application of inoculated manure proved to encourage and sustain soil health by raising the SOC, available NPK status, and uptake of nutrients by plants by reducing the BD of soil ( Tiwari et al, 2011 ; Kumar et al, 2015 , 2018a ; Kumar S. et al, 2021 ). SOC, SOC Stock, and the SOC sequestration rate were found to be influenced in a non-significant way, following the mechanism of soil buffering capacity, which shows that a soil resists the changes in its properties up to a certain period, owing to the buffering ability ( Yigini and Panagos, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement in the level of available NPK under VC + MI application might be due to enhanced nutrient release as a result of microbes-mediated accelerated decomposition and mineralization of inoculated manure ( Kuotsu et al, 2014 ; Gupta et al, 2020 ). Application of inoculated manure proved to encourage and sustain soil health by raising the SOC, available NPK status, and uptake of nutrients by plants by reducing the BD of soil ( Tiwari et al, 2011 ; Kumar et al, 2015 , 2018a ; Kumar S. et al, 2021 ). SOC, SOC Stock, and the SOC sequestration rate were found to be influenced in a non-significant way, following the mechanism of soil buffering capacity, which shows that a soil resists the changes in its properties up to a certain period, owing to the buffering ability ( Yigini and Panagos, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the ever-growing population, scarcity of arable lands, and resources alongside multiple environmental pressure, the need to focus on efficient natural resources management in agriculture for food security and sustainability is one of the biggest challenges for researchers and farming community ( Meena et al, 2021 ). To meet this challenge, environment-unfriendly agricultural chemicals, such as fertilizers, have played a significant role in green revolution and are even, today, commonly recommended to outwit nutrient deficiencies of the soils ( Kumar et al, 2018a ). The use of agro chemicals has been a major factor in improving crop production; however, it causes severe deterioration in soil health and quality and thus poses a negative impact on crop production sustainability and environmental safety ( Nelson et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research has demonstrated their adverse effects on the sustainability of crop production and environmental safety [19]. Unbalanced use of fertilizers and improper management of crop residues through burning and removal from the field are still practiced in cultivation systems [20,21]. Improper nutrient management strategy resulted in the disturbance of microbial diversity and soil fertility, making it challenging to maintain optimal soil health and plant growth [22,23].…”
Section: Agrochemistry and Prospects For Using Plant Growth-promoting...mentioning
confidence: 99%
“…Managing agro-ecosystems for sustaining enhanced productivity, farm profitability and food security, along with protecting the environment and improving soil health, enhancing C sequestration and natural resource base are the characteristics of CA. To meet this challenge, environment unfriendly agricultural chemicals, such as fertilizers, have played a significant role in Green Revolution and even today, commonly recommended to outwit nutrient deficiencies of the soils (Kumar et al, 2018). Imbalanced fertilizer use and mismanagement of crop residue via burning and removal from the field are still in practice under cereal-cereal cropping systems which cause soil and environmental pollution, nutrient mining, multi-nutrient deficiency, losses in soil bio-fertility, reduction in partial factor productivity, loss of agri-biodiversity, and ultimately, poor soil health and sub-optimal crop production.…”
mentioning
confidence: 99%